COVID-19 Infection Deteriorates the Clinical Condition and Outcomes of Acute Pancreatitis: A Meta-Analysis - Yulin Guo; Shun Hu; Xiaohui Wang; Zhe Jiang; Shuangni Duan; Feng Cao; Fei Li (Emergency Medicine International)
Backgrounds. The novel coronavirus disease 2019 (COVID-19) has caused a global pandemic. Pancreatic injuries have been reported in COVID-19 patients. The present meta-analysis was conducted to compare the morbidity and outcomes of AP between COVID-19 positive and negative patients. Methods. Databases including Cochrane Library, PubMed, and EMBASE were systematically searched (until July 3rd 2022). Studies with English abstracts comparing the severity and outcomes of AP between COVID-19 positive and negative patients were included. Mean differences or odds ratios with a 95% confidence interval were employed for assess variables. Risk of publication bias was assessed with funnel plots. Results. Data from 7 studies with a total of 2816 AP patients were included. COVID-19 positive was associated with higher incidences of pancreatic necrosis (OR = 1.65; 95% CI: 1.13 to 2.42, P = 0.01; P = 0.82 for heterogeneity) and persistent organ failure (OR = 6.87; 95% CI: 2.37 to 19.98, P = 0.0004; P = 0.12 for heterogeneity), especially cardiovascular failure (OR = 2.92; 95% CI: 1.66 to 5.14, P = 0.0002; P = 0.58 for heterogeneity) and acute respiratory distress syndrome (ARDS) or acute lung injury (ALI) (OR = 3.03; 95% CI: 2.09 to 4.39, P < 0.00001; P = 0.20 for heterogeneity). COVID-19 infection induced a higher level of CRP (MD = 0.40; 95% CI: 0.16 to 0.64, P = 0.001; P < 0.00001 for heterogeneity) as well as coagulation disorders involving platelets, prothrombin time, activated partial thromboplastin time, and D-dimer (all P < 0.05). During hospitalization, COVID-19 positive was associated with higher ICU admission rate (OR = 2.76; 95% CI: 1.98 to 3.85 P < 0.00001; P = 0.47 for heterogeneity). COVID-19 positive AP was associated with a higher mortality rate (OR = 3.70; 95% CI: 2.60 to 5.25, P < 0.00001; P = 0.12 for heterogeneity). Discussion. The number of included studies is limited and none is RCT, thus the risks of publication and selective bias could not be ignored. COVID-19 deteriorated the severity and clinical outcomes of AP, with a high incidence of morbidity and mortality.